The Impact of climate change on agriculture - Thomas, Timothy S. (AKADEMIYA2063, 2024)
Agriculture is an extremely important sector for Africa, providing a large contribution to GDP in most countries and, more importantly, representing a key source of employment in most of the continent—including 52 percent in Africa south of the Sahara in 2022 (International Labour Organization 2024)—while also serving as a bulwark against household food insecurity. Agriculture, however, is the sector most exposed to climate risk, and in years when climate conditions are not favorable, the resulting lower-than-normal agricultural production contributes to increases in food insecurity in almost every country on the continent.